Molecular Characterization of Laccase Genes from the Basidiomycete Coprinus cinereus and Heterologous Expression of the Laccase Lcc1 - Yaver, Debbie S. (American Society for Microbiology, 1999)
A laccase from Coprinus cinereus is active at alkaline pH, an essential property for some potential applications. We cloned and sequenced three laccase genes (lcc1, lcc2, and lcc3) from the ink cap basidiomycete C. cinereus. The lcc1 gene contained 7 introns, while both lcc2 and lcc3 contained 13 introns. The predicted mature proteins (Lcc1 to Lcc3) are 58 to 80% identical at the amino acid level. The predicted Lcc1 contains a 23-amino-acid C-terminal extension rich in arginine and lysine, suggesting that C-terminal processing may occur during its biosynthesis. We expressed the Lcc1 protein in Aspergillus oryzae and purified it. The Lcc1 protein as expressed in A. oryzae has an apparent molecular mass of 66 kDa on sodium dodecyl sulfate-polyacrylamide gel electrophoresis and absorption maxima at 278 and 614 nm. Based on the N-terminal protein sequence of the laccase, a 4-residue propeptide was processed during the maturation of the enzyme. The dioxygen specificity of the laccase showed an apparent K(m) of 21 ± 2 μM and a catalytic constant of 200 ± 10 min(−1) for O(2) with 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) as the reducing substrate at pH 5.5. Lcc1 from A. oryzae may be useful in industrial applications. This is the first report of a basidiomycete laccase whose biosynthesis involves both N-terminal and C-terminal processing.